Determinants of success and hemodynamic impact of balloon postdilatation of self‐expanding transcatheter aortic valves. Issue 5 (9th March 2018) - Abdelghani, Mohammad; de Winter, Robbert J.; Miyazaki, Yosuke; Modolo, Rodrigo; Tateishi, Hiroki; Cavalcante, Rafael; Sarmento‐Leite, Rogério; Mangione, José A.; Abizaid, Alexandre; Soliman, Osama I. I.; Onuma, Yoshinobu; Lemos, Pedro A.; et al.
Abstract: Objectives: To explore the rate, the determinants of success, and the hemodynamic impact of balloon postdilatation (BPD) of self‐expanding transcatheter heart valves (SE‐THVs) Background: BPD is commonly used to optimize valve expansion and reduce paravalvular leakage (PVL) after transcatheter aortic valve implantation (TAVI) without clearly knowing its hemodynamic benefits. Methods: Patients ( n  = 307) who received a SE‐THV were stratified according to whether a BPD was performed or not. Patients who received BPD were stratified according to the severity of PVL remaining after BPD into two groups: Successful BPD (≤mild PVL + BPD) and Failed BPD (moderate‐severe PVL + BPD). Results: BPD was performed in 121 patients (39.4%) and was successful in 106 patients (87.6% of attempts). A ratio of the postdilatation balloon diameter to the annulus diameter ≤0.95 was an independent predictor of BPD failure (OR: 10.72 [2.02‐56.76], P  = .005). Peak transvalvular pressure gradient (PG) was lower in the Successful BPD group (14[12‐22] mm Hg) than in the Failed BPD group (18[16‐23] mm Hg, P  = .029), and did not rise in either group during follow‐up (median [IQR], 364[161‐739] days). Conclusion: BPD was performed in 39% of patients who received a SE‐THV, and was successful in the majority of attempts. BPD failure was more likely in patients with a small postdilatation balloon‐to‐annulus diameter ratio. Effective BPD improved THV hemodynamic performance, and this was maintained in the intermediate‐term post‐TAVI.